THE EFFECTIVENESS OF VARIOUS CITRONELLA OIL NANOGEL FORMULATIONS AS A REPELLENT OF AEDES AEGYPTI MOSQUITO - SUBAGIYO, AGUS; WIDYANTO, ARIF; ARDIANSYAH, IQBAL; SAPUTRI, FIRDAUS WULAN; KURNIAWAN, DHADHANG WAHYU (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this research is to determine the effectiveness of the repellency of various citronella oil nanogel formulations against Aedes aegypti mosquito bites applied to guinea pigs. Methods: The Citronella oil nanogel was prepared by emulsification technique combined with gelling formation. The nanoemulsion formula consists of 6% Citronella oil, 10% propylene glycol, 6% combination of Tween 80 and Span 80 in variation to 4 formula, and deionized water until 100%. Nanoemulsions were then added to the gel base which is composed of Carbopol 940 and TEA. The nanogel formed was characterized physically and its effectiveness against Aedes aegypti mosquito using guinea pigs as an animal model. The repellent activity was determined by the amount of mosquito bites on the guinea pigs’s skin. Results: The organoleptic test displayed that all formulas comply with the requirements, except formula 1. The formula 2, 3, and 4 have particle size below 100 nm and the polydispersity index (PDI) less than 0.5. According to the repellent assay showed that all formulas have the effectiveness much higher than without the intervention. Formula 3 has the highest effectiveness of repellent activity against Aedes aedgypti in guinea pigs’ skin. The repellent activity of Formula 3 showed a significant difference (p-value of 0.005) as compared to nanogel without Citronella oil. Conclusion: The protective power of Citronella oil nanogel Formula 3 is the most effective as compared to the other formula.